Respuesta :

43/10 - 12/5x + 11/2 = 1/2(-18/5x + 6/5)

Do the stuff in parentheses first

43/10 - 12/5x + 11/2 = -9/5x + 3/5

Now we have to isolate the everything with an x in ine side, and the stuff without x (the variable) on the other

Do this by adding 12/5x to both sides of the equation to switch the -12/5x to the right side

43/10 - 12/5x + 12/5x + 11/2= -9/5x + 3/5 + 12/5x

43/10 + 11/2 = -9/5x + 3/5 + 12/5x

98/10 = 3/5x + 3/5

Now subtract both sides by 3/5 to switch the 3/5 to the left side

98/10 - 3/5 = 3/5x + 3/5 - 3/5

98/10 - 6/10 = 3/5x

3/5x = 92/10

Now divide both sides by 3/5

3/5x÷3/5 = 92/10 ÷ 3/5

x = (92×5)/(10×3)

x = 92/6

hope it helps, I double checked, it is correct.

just let me know uf you have any questions :)

Answer:

-3

Step-by-step explanation:

edge. Hope this helps :)

Ver imagen menciae421